PENERAPAN PEWARNA INDIGO DARI DAUN INDIGOFERA L PADA KULIT CRUST SUEDE DOMBA DENGAN TEKNIK IKAT MOTIF JUMPUTAN - Entin Darmawati; Sudarmadji Sudarmadji; Umar Santoso (Politeknik ATK Yogyakarta, 2017)
This study aims to absorb the blue Indigo dye on the skin of sheep crust suede with the technique of binding in order to produce a jumputan motif on tanned skin. Materials used were Indigo leaves (Indigofera L) and tanned leather from sheep crust suede. This research used experimental method with 3 (three) stages: (1) Making blue Indigo dye by enzyme hydrolysis process, (2) Creation of tanned leather motif with binding technique and (3) Application of blue Indigo dye on sheep crust suede using dyeing method with variations: (a) concentrations (6%; 12% and 18%); (b) dyeing time (1.5 hours, 2 hours); (c) bonding techniques (single, double and cross towards color fastness on jumputan motif pattern). The results of the color fastness were the value of 5/4, meaning good, no color changes to the original one at concentrations of 12% and 18%, time 2 hours, double bond motifs, and the value of 4/3, meaning good enough with a little faded at concentration of 6%, 2 hour time, double bond motif, and the most optimum absorption (82%) on the sheepskin's croupon. It can be concluded that the indigo dye gives blue color which can be applied to sheep crust suede with binding technique of jumputan method to produce unique and exclusive motif as raw material of leather product or craft.